Microbiological and Physiochemical Analysis of Sachet Water within Awka Metropolis - Ifionu, VC; Agu, Kingsley; Oghonim, P.AN; Uwanta, L.I; Awari, VG; Anazodo, C.A; Soludo, OC; Ojeah, I.K.; Mbachu, IAC; Okinedo, J.I (PT. Riset Press International, 2026)
Drinking water quality is one of the major significances affecting human health, lifestyle and economic well-being. Drinking water quality is solemnly dependent on the quality of source water, the treatment in water treatment plants before distributed, the water distribution system and the containers/tanks used for water storage and the household filters. This study evaluated the bacteriological, physicochemical, and heavy metal qualities of ten popular brands of sachet water commercially sold in Awka Metropolis, Anambra State, Nigeria. The aim was to assess their compliance with national and international drinking water standards and determine their potability. Standard microbiological techniques were employed to quantify microbial loads, isolate and identify bacteria, while atomic absorption spectrophotometry was used for heavy metal analysis. Physicochemical parameters were determined using standard American Public Health Association (APHA) methods. The results indicated that while the majority of the water brands were free from significant microbial contamination, two brands (FC and DS) tested positive for total coliforms, with brand FC also testing positive for faecal coliforms (E. coli), indicating faecal pollution. Bacterial isolates of public health concern included Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Enterobacter aerogenes, Staphylococcus aureus, Streptococcus faecalis, and Bacillus subtilis. Fungal counts were low but present in some samples. The physicochemical parameters (pH, turbidity, temperature, hardness, colour, and taste) for all samples were within the acceptable limits set by the WHO and NSDWQ. However, heavy metal analysis revealed alarmingly high levels of lead in one brand (FC), which exceeded the WHO permissible limit by over 12 times. The findings reveal that despite generally acceptable physicochemical qualities, some sachet water brands in Awka Metropolis pose potential health risks due to microbiological contamination and toxic heavy metals. The study recommends stricter regulatory monitoring, improved hygiene practices among producers, and public awareness to safeguard consumer health.